QARAQALPAQ ÁDEBIYATÍNDA POEMANÍŃ JANRLÍQ HÁM FORMALÍQ ÓZGESHELIGI - Mambetov, Q. (SCIENCE and SOCIETY, 2021)
The article examines the literary genre, type, genre and genre form of poem in Karakalpak literary criticism. And also given the author's conclusion of the scientific analysis of the poem, as a literary form in Karakalpak poetry.
Keywords: genre; form; kind; lyrics; epic; drama; poema